Tocotrienols In Solid Dosage Form - Cheah, Mei Mei (2014)
The bioavailability study of Tocomax® 20% powder containing mixed tocotrienols was carried out using Sprague-Dawley rats. The study showed that Tocomax® 20% powder had comparative oral bioavailability as the Tocovid® Suprabio (1.0, 1.0 and 1.2 times for alpha, gamma and delta tocotrienols respectively). In addition, it was also found to have better oral bioavailability as compared to Tocomin® 50% oily formulation (1.9, 2.4 and 2.9 times for alpha, gamma and delta tocotrienol respectively). Subsequent usage of Tocomax® 20% powder as the active ingredient for the formulation of tablets containing tocotrienols showed that a satisfactory tablet could be obtained using Neusilin UFL2 and US2 as the diluent, Ac-Di-Sol as the disintegrant and magnesium stearate as the lubricant with the ideal tablet weight of 500 mg per tablet. The tablets were homogeneous in colour and with no physical defects like capping. The tablets also have good disintegration times of approximately 8 minutes and were uniform in weight (less than 2%). The tablets with the optimized formulation were also successfully up-scaled.